ROPES Learning Model Modification to Increase Proficiency Students of Rational Thingking - ., Nizaruddin (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2010)
Mathematics teachers should have the ability mathematics, mathematical methodology skills, and ability to package the science and methodology of mathematics is a subject matter learning in school. To achieve mathematical skills that students should be equipped with skills of deductive thinking, rational, analytical, and creative. These skills are necessary for students so that they have the skills in understanding and problem-solving perspective to the prospective teacher / mathematics teacher professional. Ropes (Review, Overview, Presentation, Exercise, Summary) is a learning model that provides the opportunity for students to communicate, conduct exercises and concluded that he had learned something while under the direction of faculty. Development and modification of this learning model can be done in an effort to empower the student self-learning ability of rational thinking skills of students ?é?á Keyword: ROPES, Contextual,?é?á Rational Thinking Skills